When no means no: psychosocial dynamics of self- efficacy for refusing sexual behaviour (2009)
The study investigated between parents adolescent communication, attitude towards sexual abstinence and self-efficacy for refusing sexual behavior among adolescents in Ibadan metropolis. In a cross sectional survey, 200 adolescents were randomly sampled to respond to a structured questionnaire, their ages ranged between 11 and 20years. Result indicated that parents adolescent communication, religiosity, and attitude towards abstinence have joint influence on self-efficacy for refusing sexual behavior (F(3,197)=2.71: R2 =.21, p<.05. Also, parent adolescent communication, religiosity and attitude towards abstinence were found to independently predict self-efficacy for refusing sexual behavior. It then become pertinent that in a bid to stem the tide of HIV infection, indiscriminate sexual activities and their attendant negative consequences, parent adolescent communication should be strengthened, faith based advocacy/mobilization agents, premarital sex/marital infidelity should be adopted while attitudinal change programmes on sex education and consent should be explored.